UJI KUALITAS SUMBER AIR SEBAGAI HYGIENE SANITASI DI DAERAH PESISIR - Dian Yustika Putri Utami; Imam Suprayogi; Manyuk Fauzi (Racic : Rab Construction Research, 2024)
Tanah Merah Village, Indragiri Hilir Regency, is a village with coastal condition, brackish surface air and contains high levels of organic matter and iron. The purpose of this research is to find the best one from available water in this village to support the provision of sustainable clean water needs in the swamp area in Tanah Merah Village, Indragiri Hilir Regency, Riau Province. The method used is based on the standards of Minister of Health Regulation no. 492/Menkes/IV/2010 . The data required for this research is to use primary data by taking samples of rainwater, well water and sea water by researchers directly. From the results of tests carried out on 3 water samples, rainwater, well water and sea water, it was found that rainwater has the best clean water quality compared to well water and sea water by testing physical, chemical and microbiological parameters. So that rainwater can be used as hygiene sanitation for society in Tanah Merah Village, Indragiri Hilir Regency by collecting rainwater in every house, it can be used as a form of defense against the need for clean water